Living with HIV/AIDS among men having sex with men (MSM) in the Philippines: internet ethnography of HIV life stages - Cyruz P Tuppal; Marina Magnolia G Ninobla; Mark Donald C. Reñosa; Mara Gerbabe D Ruiz; Richard C Loresco; Shanine Mae P Tuppal; Iril I Panes (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background There is lesser attention given to Internet research using personal online blogs that can offer a valid source of information from an emic naturalistic perspective to define the meaning and essence in the life stages among men having sex with men living with HIV/AIDS in the Philippines. This study aims to capture, illuminate, and define the meaning and essence in the life stages among men having sex with men living with HIV/AIDS in the Philippines. # Methods This study utilized Internet ethnography design. A total of 16 personal online blogs were purposively sampled from Blogger and Word press, which were retracted, appraised, and saved in the word document. Through line-by-line reading and textual immersion, the meaning and essence in the life stages among men who have sex with men (MSM) living with HIV/AIDS in the Philippines were captured, illuminated, and defined. # Results The HIV life stages among MSM living with HIV/AIDS in the Philippines include Stage I Pre-HIV Exposure, Stage II HIV Exposure, Stage III Presumptive Symptomatology, Stage IV Diagnosis, and Confirmatory, and Stage V Post-HIV Diagnosis and Treatment. Accompanying each stage are the psycho-emotive components such as awareness-invincibility, familiarity-vulnerability, denial-disbelief, dispiritedness-depression, and fear-discriminant disclosure that can be addressed by the relational agency's distinct but interrelated values system. '*I am still me*' is the overall representation of the meaning and essence in the life stages among MSM living with HIV/AIDS in the Philippines. # Conclusion The fight against the disease does not offer a one-size-fits-all strategy but should be holistic, comprehensive, integrative, humanistic, and compassionate. From then, we could say---we are arriving at "the end of stigma." "We are ONE" and "We are in communion in caring with PLWHA" must be revitalized into national and global agenda.